2017
DOI: 10.1101/221879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification of directed gene networks using large-scale population genomics data

Abstract: Identification of causal drivers behind regulatory gene networks is crucial in understanding gene function. We developed a method for the large-scale inference of gene-gene interactions in observational population genomics data that are both directed (using local genetic instruments as causal anchors, akin to Mendelian Randomization) and specific (by controlling for linkage disequilibrium and pleiotropy). The analysis of genotype and whole-blood RNA-sequencing data from 3,072 individuals identified 49 genes as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 96 publications
2
19
0
1
Order By: Relevance
“…The majority (86%) of the target CpGs were located on the q-arm of chromosome 19. We found that for most of these CpGs (92%) their DNA methylation levels were associated with the expression levels of one or more nearby zinc fingers (table S13-14), consistent with previous gene network analyses (Luijk et al, 2018). Although SENP7 has no DNA-binding properties, previous research has shown that it exerts its effect through deSUMOylation of the chromatin repressor KAP1 (Garvin et al, 2013).…”
Section: Senp7supporting
confidence: 89%
See 4 more Smart Citations
“…The majority (86%) of the target CpGs were located on the q-arm of chromosome 19. We found that for most of these CpGs (92%) their DNA methylation levels were associated with the expression levels of one or more nearby zinc fingers (table S13-14), consistent with previous gene network analyses (Luijk et al, 2018). Although SENP7 has no DNA-binding properties, previous research has shown that it exerts its effect through deSUMOylation of the chromatin repressor KAP1 (Garvin et al, 2013).…”
Section: Senp7supporting
confidence: 89%
“…Second, closer inspection of proteins that do not have DNA-binding properties suggests that they may regulate DNA methylation through protein-protein interactions. Possible mechanisms include post-translational regulation (NFKBIE encodes for IκBε which retains NF-kB in the cytoplasm (Bonizzi and Karin, 2004)), post-translational modification (SENP7: deSUMOylates the repressor KAP1 (Luijk et al, 2018)) and recruitment of epigenetic proteins to specific target sites through association with a DNA-binding protein (NLRC5 associates with a protein complex in MHC-I region (Kobayashi and van den Elsen, 2012)). Third, a fraction of the identified genes overlap with genes in a database that focuses on the core epigenetic regulators (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations